The impact of viscous behavior on thermo-mechanical fatigue life of cylinder head using two-layer viscoplasticity model - Ashouri , Hojjat (Archive of Mechanical Engineering, 2026)
The cylinder head is a fundamental and challenging part of an engine, in which the thermo-mechanical stresses due to fatigue effectively contribute to its damage and reduction of its fatigue life. This study investigated the effect of viscous behavior on the thermomechanical fatigue life of a cylinder head using the Sehitoglu model, with the finite element method employed for the analysis. The ABAQUS software was also used to predict temperatures, stresses, and thermomechanical fatigue life using the Sehitoglu model and the FEMFAT software. Moreover, a two-layer viscoplasticity model was employed to account for the cylinder head’s viscous behavior. Low-cycle fatigue tests were carried out at various temperatures to characterize the viscous and mechanical behavior of the aluminum-silicon-magnesium alloy. The finite element analysis suggested that the maximum temperature of 308◦C and the maximum stress of 136 MPa occurred at the valve bridge. The fatigue life analysis revealed that neglecting viscous behavior led to a 657-cycle (8.9%) overestimation of fatigue life, emphasizing the importance of incorporating viscous behavior into the thermo-mechanical fatigue life analysis.